2022
DOI: 10.7759/cureus.22990
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality Among Men in Russia: A Review of Recent Epidemiological Data

Abstract: Suicide is a phenomenon that is not related to a specific class of countries but is a problem worldwide. Many studies have attempted to explain gender differences in suicidal behaviors. Unfortunately, Russia holds the world's top place for the number of suicides committed by its male citizens. Russia is still demonstrating unusually high death rates due to non-natural causes, and these demographic trends are concerning. We analyzed suicidality among men in Russia over the past 20 years using official data publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…These findings are consistent with the general understanding that depression and bipolar depression are the most evident contributors to suicidal ideation and suicidality risks[61,64]. It is an interesting fact that many studies indicate alcohol use to be a particular suicidal risk factor, particularly in the Russian Federation and in relation to alcohol overconsumption; whilst our results support this data, according to our sample analysis, alcohol misuse was outranked by the use of illicit psychoactive compounds[33,65]. Consistent with international findings from many Asian studies we found that recent changes in certain other mental health-associated variables, such as the recent increase in suicidal thoughts, deterioration of sleep quality with the need to use sleeping pills, and having nightmares due to COVID-19-related pandemic contexts are also associated with higher current suicidality risks[10,62,67,68].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with the general understanding that depression and bipolar depression are the most evident contributors to suicidal ideation and suicidality risks[61,64]. It is an interesting fact that many studies indicate alcohol use to be a particular suicidal risk factor, particularly in the Russian Federation and in relation to alcohol overconsumption; whilst our results support this data, according to our sample analysis, alcohol misuse was outranked by the use of illicit psychoactive compounds[33,65]. Consistent with international findings from many Asian studies we found that recent changes in certain other mental health-associated variables, such as the recent increase in suicidal thoughts, deterioration of sleep quality with the need to use sleeping pills, and having nightmares due to COVID-19-related pandemic contexts are also associated with higher current suicidality risks[10,62,67,68].…”
supporting
confidence: 92%
“…However, the number of suicide attempts was apparently higher among females [35,36]. According to the most recent review about suicides in Russia, the number of suicide attempts increases with age, with its peak at 50 years old [33].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite a recent decline in suicide mortality in the Russian Federation ( 43 ) following changes in government alcohol policy ( 44 ), pre-pandemic suicide rates in the country remained higher than the European regional average ( 45 ). Rates of depression in the Russian general population were also high before the pandemic.…”
Section: Discussionmentioning
confidence: 99%